Participatory training for real! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
François Benao of Léo, Burkina Faso, follows up a letter from Sirad Seied Yesut in Spore 83 about 'how CTA should democratise (excuse my choice of word!) the seminars and training workshops it supports. Those of us working at the grassroots in...